2016
DOI: 10.1007/s00395-016-0592-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cardiovascular risk factors associated with bone marrow cell subsets in patients with STEMI: a biorepository evaluation from the CCTRN TIME and LateTIME clinical trials

Abstract: Autologous bone marrow mononuclear cell (BM-MNC) therapy for patients with ST-segment elevation myocardial infarction (STEMI) has produced inconsistent results, possibly due to BM-MNC product heterogeneity. Patient-specific cardiovascular risk factors (CRFs) may contribute to variations in BM-MNC composition. We sought to identify associations between BM-MNC subset frequencies and specific CRFs in STEMI patients. Bone marrow was collected from 191 STEMI patients enrolled in the CCTRN TIME and LateTIME trials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…This mechanism was shown already 12 years ago to be associated with progression in atherosclerosis and coronary artery disease ( Werner et al, 2005 ). Recently, the investigation of responders to cardiac repair in the CCTRN-trials obtained similar findings in bone marrow of BMDC treated non-responsive chronic ischemic heart failure patients ( Bhatnagar et al, 2016 , Contreras et al, 2017 ). In the PERFECT trial we found a striking difference in cardiac recovery between responders and non-responders.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This mechanism was shown already 12 years ago to be associated with progression in atherosclerosis and coronary artery disease ( Werner et al, 2005 ). Recently, the investigation of responders to cardiac repair in the CCTRN-trials obtained similar findings in bone marrow of BMDC treated non-responsive chronic ischemic heart failure patients ( Bhatnagar et al, 2016 , Contreras et al, 2017 ). In the PERFECT trial we found a striking difference in cardiac recovery between responders and non-responders.…”
Section: Discussionmentioning
confidence: 68%
“…Yet, in these trials, clinically relevant improvements of LVEF as well as non-responsive patients were observed both in treatment and placebo groups ( Henry et al, 2016 , Nasseri et al, 2014 , Bartunek et al, 2016 ). This has raised the question of induction of reparative mechanisms independent of stem cell application and potential suppressive factors of vascular repair associated with CD34 + Endothelial Progenitor Cells (EPC) ( Werner et al, 2005 , Taylor et al, 2016 , Bhatnagar et al, 2016 , Contreras et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Gap19 inhibits HC currents by perturbing CT interaction with a cytoplasmic loop (CL)-located binding site, which is necessary for Cx43 HC opening (reviewed in [ 13 ]). Making use of Gap19, we demonstrated protection against cardiac ischemia/reperfusion injury and cardiomyocyte cell death [ 6 , 14 ]. Gap19 is increasingly used to probe for Cx43 HC involvement in various cardiac, brain, and other disease models [ 7 , 8 , 15 , 16 , 17 , 18 ], making a more detailed analysis indicated and timely.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Ly6C lo M2 macrophages express and release anti-inflammatory cytokines such as VEGF and TGF-β, contributing to CF activation, angiogenesis and wound healing 76 . In addition, infusion of IL-10 in vivo significantly increased the expression of M2 marker genes along with CF activation (as evidenced by CF proliferation, recruitment and ECM accumulation), and ultimately led to the improvement of cardiac remodeling both structurally and functionally 77 . A recent study using flow cytometry and RNA sequencing technology successfully mapped the transcriptomes of polarized macrophage during the first week post MI 78 : within the first day post MI, macrophages showed the unique features of pro-inflammatory proprieties and ECM degradation, while the macrophages on day 3 displayed the upregulation of proliferation and phagocytosis as well as the reprogramming of metabolism; macrophages on days 7 exhibited proreparative signatures characterized by the elevation of Col1a1, Col3a1, and postn expression.…”
Section: Immune Cellsmentioning
confidence: 99%